Pelatihan Tegnologi Tepat Guna (TTG) Pembuatan Pupuk Kompos Desa Toto Harjo Kecamatan Purbolinggo - Novita Novita; Sri Indaryati; Novia Ambar Sari; Eny Ivan’s; Wintari Mandala (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Appropriate Technology is a trantition application from the traditional technology to modern technology. Appropriate Technology is designed by adapting the enviromental, cultural, social, political and economic society with simple principles, affordable and easy to implemnet. Toto Harjo village has good agricultural potential. In order to improve the quality of agricultural land and also deal with household waste that is nt used properly. Community service activities are carried out by providing education about making compost fertilizer that utilizes organic waste form local farmers household. Implementation of community service activities is carried out trough 3 stages, the preparation stage, implementation stage and evaluation stage. The preparatory stages were carried out by making direct observations in Toto Harjo Village regarding organic waste processing problems. In the implementation stage, activities were carried out involving 26 Toto Mulyo Village farmers. The activity was carried out by providing material on how to process organic fertilizer from household waste using the stacked bucket method and practiced directly, which was actively followed by the farmers of Toto Mulyo Village. Evaluation activities are carried out by distributing questionnaires containing participants' understanding and satisfaction with the service activities carried out. The results of the questionnaire show that the community really understands and hopes that similar activities can continue to be carried out